PT. ERUDEYE INDONESIA’S PAZCAL CLOUD LAUNCHING ACTIVITY REPORT (PROGRAM MANAGER) - Koesfarmasiana, Ardini; Setyabudi, Djoko; Pradekso, Tandiyo; Ulfa, Nurrist Surayya (Interaksi Online, 2015)
Cloud Computing is a technology that utilizes internet and central remote servers to govern or to manage the data and applications. The potential of cloud computing growth in Indonesia is widely open, however cloud computing market in Indonesia is still dominated by giant companies such as Microsoft and Telkom. Aware of its potential, PT. erudeye Indonesia develops cloud computing service called Pazcal Cloud, must undertake precise action as part of the major activities of marketing communication for Pazcal Cloud product, so that Pazcal Cloud gets attention and product position in the mind of market target.Based on situation analysis, SWOT and theories consideration, several promotional actions are chosen as the way to introduce Pazcal Cloud to the target audience. The actions are Search Engine Optimization (SEO), IT-based article writing, Pazcal trial version testimony video, “PaaS for Quick Development, Collaboration & Deployment” webinar and “Rainbow Rendezvous: Boost Your Experience With Pazcal” seminar. The main target comes from IT enterprises that are located in DKI Jakarta. The whole activities are divided into three stages, namely: 1) Positioning Stage, 2) Educating Stage, and 3) Strengthening Position Stage.These promotional activities are an attempt to increase the awareness of the target audience of Pazcal Cloud and place it as an efficient and reliable cloud computing product. Therefore, Program Manager position is one of the most important components in the managerial team for this activity. This position is meant to manage the program plan as well as to execute the program. With the coordination, adequate creativity, as well as concise decision making ability, the tasks on this position can be done successfully.